Perspectivas simbólicas de construção identitária através do consumo on-line no Brasil: uma análise qualitativa sobre o segmento automotivo - Araújo Neto, José Onofre de (2010)
This dissertation aims to investigate more deeply the issues related to internet use for consumption, with reference to a repertoire capable of offering a perspective that reflects opportunities for interpretation of the use of this technology beyond its functional capabilities immediately perceived by users. The relationship between the functional classified as such convenience, speed, connectivity, volume of information, among many others, and issues tied to the use of this technology and through this technology, has been studied in a qualitative approach. The use of qualitative methodology, specifically the one related to the focus groups the so-called discussion groups was associated with the analysis of theoretical classical thinkers´ production who have worked the theme of identity through the construction of Western thought. The results obtained in the study indicated the existence of other values associated with the use of the Internet, not only those related to the objective function by such technology, but also social rewards not as obvious as adjustment, belonging, contemporary, among other characteristics that distinguish and allow the individual to attend the summit the contemporary features that can be set and associated to him as his party and expression